PENGARUH PROFESIONALISME, AMBIGUITAS PERAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR (Studi Empiris pada KAP di Kota Surakarta dan Yogyakarta) - Ine Noviana Putri; Rispantyo Rispantyo; Bambang Widarno (Universitas Slamet Riyadi, 2020)
This isresearch was conducted toodetermine theeeffect off professionalism,role ambiguity, organizational commitment on the auditor performance. Thisstudy uses primary data from the answers to questionnaires distributed toauditors at KAP in Surakartas and Yogyakarta. The sampling technique was takenusing purposivensampling method, amounting too32 respondent. Data analysistechniques used in this study were descriptive statistical tests, validity tests,reliability tests, classic assumption tests, multiple linear regression analysis tests,t tests, F tests, and determination tests (R2). Based on the results of data analysisthe effect of professionalism on the auditor performance obtained a positivecoefficient and significant effect. Thee effect off role ambiguity onn the tendencyauditor performancee obtained negative coefficient and significant effect. Theeffectnofforganizationaliscommitmentoon the auditorsperformance is obtainedpositive coefficient and significant effect. The suggestion in this research is toincrease the research object, namely not only KAP in Surakarta and YogyakartaCity and to add moderating or intervening variables.